Association of Streptococcus gallolyticus subspecies gallolyticus with colorectal cancer: Serological evidence. Issue 7 (20th November 2015) - Butt, Julia; Romero‐Hernández, Beatriz; Pérez‐Gómez, Beatriz; Willhauck‐Fleckenstein, Martina; Holzinger, Dana; Martin, Vicente; Moreno, Victor; Linares, Cristina; Dierssen‐Sotos, Trinidad; Barricarte, Aurelio; Tardón, Adonina; Altzibar, Jone M.; et al.
Abstract : The colonic opportunist Streptococcus gallolyticus subspecies gallolyticus (SGG) is potentially associated with colorectal cancer (CRC). Large‐scale seroepidemiological data for SGG antibodies and their possible association with CRC is currently missing. Associations between CRC and antibody responses to SGG were examined in 576 CRC cases and 576 controls matched by sex, age and province from a population‐based multicase–control project (MCC‐Spain). MCC‐Spain was conducted between 2008 and 2013 in 12 Spanish provinces. Antibody responses to recombinant affinity‐purified SGG pilus proteins Gallo1569, 2039, 2178 and 2179 were analysed by multiplex serology. Polyomavirus (PyV) JC VP1 and PyV 6 VP1 proteins served as disease‐specificity controls. In the control population, antibody responses to pilus proteins were mostly weak. Antibody responses to individual pilus proteins Gallo2039 (OR: 1.58, 95% CI: 1.09–2.28), Gallo2178 (OR: 1.58, 95% CI: 1.09–2.30) and Gallo2179 (OR: 1.45, 95% CI: 1.00–2.11) were significantly associated with CRC risk. The association was stronger for positivity to two or more pilus proteins of Gallo1569, Gallo2178 and Gallo2179 (OR:1.93, 95% CI: 1.04–3.56) and for double‐positivity to Gallo2178 and Gallo2179 (OR: 3.54, 95% CI: 1.49–8.44). The association between SGG infection and CRC risk was stronger among individuals younger than 65 years. For the first time we demonstrated a statistically significant association of exposure to SGG antigens and CRC in a large seroepidemiological study. These results should stimulate further studies on the role of SGG in CRC pathogenesis. Abstract : What's new? The colonic opportunistic Streptococcus gallolyticus subspecies gallolyticus (SGG) is potentially associated with colorectal cancer (CRC). Large‐scale seroepidemiological data for SGG antibodies and their possible association with CRC are however currently lacking. Using SGG pilus proteins Gallo1569, Gallo2039, Gallo2178 and Gallo2179 as antigens for multiplex serology in a population‐based case–control study, here the authors for the first time demonstrate a significant epidemiological association of antibodies to SGG antigens with CRC. SGG serology might thus provide a marker to identify a subgroup of patients at increased risk of CRC. Studies on the potential role of SGG infection in CRC development appear warranted.